Can Sclerotinia stem and root rot be managed effectively without causing environmental imbalance in soil? - Mihajlović, Milica; Rekanović, Emil; Hrustić, Jovana; Grahovac, Mila; Stevanović, Marija; Tanović, Brankica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Sclerotinia stem and root rot, caused by Sclerotinia sclerotiorum, is considered to be an important soil-borne disease of over 400 plant species, including a wide range of species important for agriculture. In vitro and in vivo sensitivity of S. sclerotiorum to several commercial fungicides and biofungicides was studied. The highest efficacy was achieved by boscalid (98%) and fluopyram (80%), and the lowest by a B. subtilis-based product (5%). The isolate was sensitive to all tested products in vitro. Considering the tested synthetic fungicides, fluopyram exhibited the highest toxicity (EC50=0.003 mg/l), while captan exhibited the lowest (EC50=8.94mg/l). Even lower efficacy was achieved by tea tree oil and B. subtilis-based products. The environmental impact of pesticides and biopesticides used for Sclerotinia control was assessed. Modeling of predicted environmental concentrations in soil (PECsoil), coupled with literature toxicity data, served for assessment of pesticides soil risks. A high long-term risk for earthworms was revealed for captan and thiophanate-methyl. Based on both efficacy and risk assessment results, fluopyram was found to have the best properties of all tested conventional pesticides, while tea tree oil exerted better performance than the Bacillus product. Further investigation of combined use of conventional and biopesticides might reveal new perspectives regarding effective Sclerotinia control, while simultaneously reducing negative environmental impact.